ANALISIS PERSPEKTIF GENDER DALAM POLA PERILAKU PURNA MIGRAN PEREMPUAN DI SRAGEN - Rahmawati, Ratih; Demartoto, Argyo; Soemanto, RB (Jurnal Analisa Sosiologi, 2017)
Woman’s migrant retirement identical as an unskilled labor, minimal in knowledge and skill, therefore they only rely on remittance to fulfilthe necessities of life. But after empowerment conducted to do poductive activities we can see there’s transformation on behaviour pattern that woman’s migrant retirement perceive. On one side they have income so that they can increase family welfare, but on the other hand woman’s migrant retirement feel the effect of the empowerment that being held.The aim of this research is to know the behaviour pattern of woman’s migrant retirement at Sragen City, Indonesia which analyze by gender perspective theory. This research using qualitative methods with case study approach, in-depth and holistic data processing through observation, interview and documentation.The result of this study show that, woman’s migrant retirement kept their family welfare the same as the time before they were migrant workers. The strategy that woman’s migrant retirement do is to harness their income to be bussines financier and form a social networking that include poductive activities that can increase the income.Such activities are done as a collective group which include goat livestock, catering, vegetable’s base food production, and craft. Woman’s migrant retirement have a bussines group that ensure of equality right of bussines so that lifesyle change took place on woman’s migrant retirement. At this empowerment process woman’s migrant retirement did not experience marginalization and did not suffered form violation. But they undergone double burden because majority of them were housewife that has obligation to take care their husband and child. Woman’s migrant retirement.Keywords: Gender Analysis, Behaviour Pattern, Woman’s Migrant Retirement.AbstrakPurna migran perempuan identik dengan tenaga yang kurang terampil, minim pengetahuan dan keahlian sehingga hanya mengandalkan remitan untuk memenuhi kebutuhan hidup.Namun setelah diadakan pemberdayaan dengan melaksankaan kegiatan produktifterdapat transformasi pola perilaku yang dirasakan oleh purna migran perempuan. Disatu sisi mereka memiliki pendapatan sehingga dapat meningkatkan kesejahteraan keluarga, namun disisi lain purna migran perempuan merasakan dampak-dampak dari diadakannya pemberdayaan tersebut. Penelitian ini bertujuan untuk  mengetahuipola perilaku purna migran perempuan di Sragen Indonesia yang dianalisis dengan teori perspektif gender. Penelitian kualitatif dengan pendekatan studi kasus ini mengolah data secara mendalam dan menyeluruh melalui observasi, wawancara dan dokumentasi.Hasil penelitian menunjukkan bahwa purna migran perempuan menjaga kesejahteraan keluarga seperti ketika menjadi migran.Strategi yang dilakukan purna migran perempuan adalah memanfaatkan pendapatan secara optimal dijadikan modal usaha dan membentuk suatu jaringan sosial yang didalamnya berisi kegiatan produktif yang dapat menambah penghasilan.Kegiatan yang dilakukan secara berkelompok seperti ternak kambing, catering makanan, produksi makanan olahan dari sayur-sayuran, serta produksi kerajinan tangan. Purna migran perempuan yang memiliki kelompok usaha telah memiliki hak-hak yang setara dalam memiliki pekerjaan sehingga perubahan gaya hidup terjadi dalam diri purna migran perempuan. Pada proses pemberdayaan purna migran perempuan tidak mengalami marginalisasi serta tidak mengalami tindakan kekerasan. Namun mereka mengalami beban ganda sebab mayoritas dari mereka ibu rumah tangga yang memiliki kewajiban untuk mengurus suami dan anak. Purna migran perempuan tidak mengalami stereotype atau pelabelan ketika melaksanakan kegiatan produktif.Kata Kunci: Analisis Gender, Pola Perilaku, Purna Migran Perempuan.